Meta Evaluation: On The Evaluation of Academic Services and Facilities at FKIP Baturaja University - Dewi Lestari; Novarita Novarita; Undang Rosidin (Journal of Educational Research, Evaluation and Supervision, 2024)
The success of universities in achieving their vision and mission is determined by student satisfaction with the services provided by universities. This study aims to reveal the quality of college services to students. Through a qualitative approach, this researcher uses data sources in the form of questionnaires that are surveyed to students and then processed descriptively, which are converted in the form of a rating scale. The target of the student satisfaction survey on university services is active students at Baturaja University, involving 797 people from the total number of students (the student body). The data collected were in the form of questionnaires distributed to five faculties and one postgraduate program. The method used in this research is the survey method. A survey is one type of research used to examine the symptoms of a group or individual behavior. In surveys, data collection generally uses a questionnaire as a data collection tool with the aim of knowing who, what the respondent thinks, feels, or the tendency of an action. The results of this study indicate that the level of student satisfaction with Baturaja University services in each faculty, in general, for 4 service categories is in the moderately satisfactory category.